Stationary Light in Atomic Media. Issue 5 (30th April 2019) - Everett, Jesse L.; Higginbottom, Daniel B.; Campbell, Geoff T.; Lam, Ping Koy; Buchler, Ben C.
Abstract: When ensembles of atoms interact with coherent light fields, a great many interesting and useful effects can be observed. In particular, the group velocity of the coherent fields can be modified dramatically. Electromagnetically induced transparency is perhaps the best known example, giving rise to very slow light. Careful tuning of the optical fields can also produce stored light where a light field is mapped completely into a coherence of the atomic ensemble. In contrast to stored light, in which the optical field is extinguished, stationary light is a bright field of light with a group velocity of zero. Stationary light has applications in situations where it is important to maintain an optical field, such as attempts to engineer large nonlinear interactions. In this paper, the stationary light demonstrations published to date are reviewed and a unified theoretical framework that describes the experimental observations is provided. Possible applications of stationary light are also discussed, with a particular focus on all‐optical phase gates for quantum information technology. Abstract : Coherent atom–light interactions can strongly modify the propagation of light. This paper reviews the development of experimental schemes that generate "stationary light" in atomic ensembles and provides a unified theoretical framework to describe experimental observations. Also discussed is the potential for stationary light to generate large nonlinear optical phase shifts for quantum information processing.